A NEW WORLD WAR CAN BEGIN OR HAS ALREADY BEGUN? - Romanyuk, Oleksandr (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2024)
The article examines the problem of clarifying the essence of world wars, which is relevant in the current conditions of international relations. For a long time, the World War I (1914-1918) and World War II (1939-1945) were considered such wars. The consequences and impact of Russia’s war against Ukraine, which began in 2014 and became widespread in 2022, on the renewal of disputes about the essence of world wars are investigated, since other countries began to participate indirectly in it on the side of both one side and the other. Attention is focused on two points of view within the discussion regarding the spread of the Russian-Ukrainian war to international relations. The essence and content of both points of view are revealed, which directly relate to the issue of the Third World War and the role of the Russian-Ukrainian war in its beginning. The first point of view is that Russian aggression against Ukraine threatens to start World War III. The second point is a new world war has begun, as the Russian-Ukrainian military confrontation causes not only military support from other states, but also an escalation of conflicts in other parts of the world. In the Middle East, the confrontation has already taken on the character of a war, involving Israel, Iran and its proxies, as well as Turkey’s proxies. Military action is unfolding in Africa, where autocratic regimes supported by Russia are fighting opposition movements. Tensions are rising in the Far East, thanks to North Korea’s aggressive stance and communist China’s claims to Taiwan. The author of this paper, analyzing the current state of international relations, believes that a new world war has already begun. The theoretical and methodological basis for such a conclusion is his division of world wars into classical and post-classical. He considers the World War I and World War II to be classic, and he defines the Cold War and the growing war between democracies and autocracies in the modern world as post-classic. The main differences between classical and post-classical world wars are analyzed. The main reason for the transition of world wars from the classical stage to the post-classical stage was the appearance of atomic weapons.